Development of a Predictive Model to Induce Atherogenesis and Hepato-Renal Impairment in Female Rats - Lucas Pires Guarnier; Paulo Vitor Moreira Romão; Rhanany Alan Calloi Palozi; Aniely Oliveira Silva; Bethânia Rosa Lorençone; Aline Aparecida Macedo Marques; Ariany Carvalho dos Santos; Roosevelt Isaias Carvalho Souza; Karine Delgado Souza; Emerson Luiz Botelho Lourenço; Arquimedes Gasparotto Junior (Biomolecules, 2019)
Therapeutic approaches for the treatment of dyslipidemia and atherosclerosis have radically changed in recent decades. Part of this advance undeniably stems from basic biomedical research that has provided a better understanding and identification of new therapeutic targets. The aim of this work was to develop a model to induce atherogenesis and hepato-renal impairment in female Wistar rats. The following groups received the respective treatments for 60 days: control animals, non-ovariectomized rats that received an atherogenic diet (NEAD), ovariectomized rats that received an atherogenic diet (NOAD), non-ovariectomized rats that received an atherogenic diet and oral Nω-nitro-l-arginine methyl ester hydrochloride (l-NAME; LEAD), and ovariectomized rats that received an atherogenic diet and oral l-NAME (LOAD). Animals in the NEAD, NOAD, LEAD, and LOAD groups also received methimazole and cholecalciferol daily. Urinary, biochemical, hemodynamic, and electrocardiographic parameters and renal function were assessed. Samples of the liver, heart, kidney, and arteries were collected to investigate redox status and perform histopathological analyses. All of the groups developed dyslipidemia and hepatic steatosis. Only the NEAD group developed arterial lesions that were compatible with fatty streaks. Renal function was significantly impaired in the LEAD and NOAD groups. These results indicate a viable alternative to induce atherogenesis and hepato-renal impairment in female rats.